2012
DOI: 10.1016/j.celrep.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

FGF Regulates TGF-β Signaling and Endothelial-to-Mesenchymal Transition via Control of let-7 miRNA Expression

Abstract: Summary Maintenance of normal endothelial function is critical to various aspects of blood vessel function but its regulation is poorly understood. In this study we show that disruption of baseline FGF signaling to the endothelium leads to a dramatic reduction in let-7 miRNA levels that in turns increases expression of TGFβ ligands and receptors and activation of TGFβ signaling leading to endothelial-to-mesenchymal transition (Endo-MT). We further find that Endo-MT is an important driver of neointima formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
332
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(357 citation statements)
references
References 39 publications
21
332
1
3
Order By: Relevance
“…miR-125 isoforms can also repress SMAD4 in human ESCs to favor neural commitment during neural conversion (Boissart et al 2012). let-7 family members inhibit TGFBR1 to prevent endothelial-to-mesenchymal transition, while, in chicken embryos, down-regulation of let-7 permits active ACVR2 to contribute to gastrulation (Bobbs et al 2012;Chen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…miR-125 isoforms can also repress SMAD4 in human ESCs to favor neural commitment during neural conversion (Boissart et al 2012). let-7 family members inhibit TGFBR1 to prevent endothelial-to-mesenchymal transition, while, in chicken embryos, down-regulation of let-7 permits active ACVR2 to contribute to gastrulation (Bobbs et al 2012;Chen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expression levels of let-7 and Lin28 are inversely correlated (29). Recently, it was found that under normal conditions, let-7 maintains low levels of TGF-␤R1 expression in human umbilical vein endothelial cells and in adult human liver cells (30,31). In addition, in tubular epithelial cells, lipoxins were shown to down-regulate TGF-␤R1-induced fibrosis by up-regulating let-7c (32).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Primary mouse endothelial cells were isolated from the heart, lung, and liver by using rat anti-mouse CD31 antibody (clone MEC13.3, Pharmingen; 553370) and Dynabeads (catalog no. 110.35; Invitrogen) as described (25).…”
Section: A B C D Ementioning
confidence: 99%
“…The lysates were centrifuged at 15,871 × g at 4°C for 15 min. The immunoprecipitation and Western blot analysis procedure were described (25).…”
Section: A B C D Ementioning
confidence: 99%